Social and Economic Impact of Urban Migration: A Qualitative Study in Large Cities - Godlif Sianipar; Olyvia Rosalia; Firayani (Nomico, 2025)
This research delves into the complexities surrounding the integration of migrants in Medan's urban environment, highlighting the obstacles they face in social adaptation, their contributions to the local economy, and the rising socio-economic frictions. The study indicates that cultural disparities, resistance from local populations, and the prevalent urban individualism impede smooth social integration. Migrants often retreat into informal networks as a coping mechanism against exclusion, which, while providing safety, also reinforces societal divisions. Economically, migrants significantly impact the informal sector, driving small-scale entrepreneurial activities, yet their progress is hindered by challenges such as inadequate financial resources, legal recognition, and insufficient social safeguards. Additionally, the competition for low-paying jobs between migrants and locals fuels tension, further entrenching economic disparities. These issues are aggravated by a lack of inclusive urban planning and policies. The study advocates for proactive policy measures aimed at fostering cross-cultural engagement, enhancing migrant business sustainability, and ensuring equal access to resources, infrastructure, and social protection to ensure a more inclusive and equitable urban future.